A legal study on the protection of rights of married children / Suraya Hani Salim … [et al.] - Amrah, Nurhamimah; Khairunnisa Mohd Roslan, Siti Hawa; Hani Salim, Suraya; Latin, Yuhailly (2011)
This research is conducted for the purpose of emphasizing the importance of having a law that provides protection for young spouses with regard to the issue of child marriage. Besides that, the research is also conducted to provide various information on how the rights of these children would be violated if they involve in such practice. This research also scrutinized the existing law in Malaysia and its lacking besides giving a few examples of existing laws in other countries (India, Pakistan and Afghanistan). This research is conducted through library research that includes primary and secondary sources as well as interviews with a lecturer. The importance of this research is to provide guidelines, recommendations and suggestions as an addition or supplement to the existing law in Malaysia as well as to create awareness on how great the impact of child marriage if the rights and the welfare of the children are not protected.